Methodology for improving the body balance of athletes in acrobatic rock'n'roll at the stage of preliminary basic training - Artemyeva, H.; Moshenska, T.; Panshyna, A.; Medvediev, Y. (Slobozhanskyi herald of science and sport, 2020)
An analysis of the content of the competitive programs of various categories of athletes in acrobatic rock'n'roll (sports couples and formation teams) allows us to determine that all motor activity occurs in complicated and sometimes extreme conditions with a constant change in body position in three planes: sagittal, frontal and horizontal. Given this, we can say that for a rational construction of the technique of motor actions, athletes are constantly faced with the need to restore and maintain the balance of the body, which has a close interaction with the general level of physical preparedness [1; 2; 4; 10; 12]. Based on the analysis of literary sources, we can state that at this stage in the development of acrobatic rock'n'roll there are too few scientific and methodological literature on the issues of purposeful and proportionate development of the ability of athletes to maintain body balance, as one of the determining factors for successful mastery of the technique of acrobatic rock'n'roll. This fact reduces the effectiveness of the training process of athletes.